Microbiomes in action: multifaceted benefits and challenges across academic disciplines - Soth, Sereyboth; Hampton, John G.; Alizadeh, Hossein; Wakelin, Steve A.; Mendoza-Mendoza, Artemio (Frontiers in Microbiology, 2025)
Microbiomes combine the species and activities of all microorganisms living together in a specific habitat. They comprise unique ecological niches with influences that scale from local to global ecosystems. Understanding the connectivity of microbiomes across academic disciplines is important to help mitigate global climate change, reduce food insecurity, control harmful diseases, and ensure environmental sustainability. However, most publications refer to individual microbiomes, and those integrating two or more related disciplines are rare. This review examines the multifaceted benefits of microbiomes across agriculture, food manufacturing and preservation, the natural environment, human health, and biocatalyst processes. Plant microbiomes, by improving plant nutrient cycling and increasing plant abiotic and biotic stress resilience, have increased crop yields by over 20%. Food microbiomes generate approximately USD 30 billion to the global economy through the fermented food industry alone. Environmental microbiomes help detoxify pollutants, absorb more than 90% of heavy metals, and facilitate carbon sequestration. For human microbiomes, an adult person can carry up to 38 trillion microbes which regulate well being, immune functionality, reproductive function, and disease prevention. Microbiomes are used to optimize biocatalyst processes which produce bioenergy and biochemicals; bioethanol production alone is valued at over USD 83 billion p.a. However, challenges, including knowledge gaps, engaging indigenous communities, technical limitations, regulatory considerations, the need for interdisciplinary collaboration, and ethical issues, must be overcome before the potential for microbiomes can be more effectively realized.